Study the effect on activity of alumina supported CuO-CeO2-ZrO2 catalysts prepared by four methods for CO oxidation - Rattan G.; Prasad R. (My University, 2025)
In the present study four catalysts, prepared by four different methods i.e. co- impregnation, citric acid sol-gel, urea nitrate combustion and urea gelation co- precipitation methods, have been used to study the effect of CO oxidation. The precursor Cu(NO3)2 3H2O has been used as for the preparation of catalysts having the composition CuCe5.17Zr3.83Ox/γ-Al2O3(25wt%). Catalysts were calcined at 5000C and characterized by BET, XRD, TGA/DSC and SEM. A fixed weight (100 mg) of the catalyst was taken in a tubular fixed bed reactor at atmospheric pressure. 2.0% CO in air at a total feed rate of 60 ml/min was used in the reactor. The oxidation of CO to carbon dioxide was carried out at temperature ambient to 280°C. The preparation methods effect the catalytic activity of the catalysts as is discussed in the results. Excellent activity for CO oxidation is shown by the catalyst prepared by sol - gel method followed by co-impregnation, urea gelation and urea nitrate combustion methods. It exhibited the total conversion at 210°C. All the four catalysts prepared did not show any deactivation activity for 50 hours of continuous runs.